PENGARUH KEPUASAN KERJA DAN STRESS KERJA TERHADAP TURNOVER INTENTION PADA PT. HASNUR RIUNG SINERGI KABUPATEN TAPIN - Agustinus Kevin Alfarol; Jaya Bahwiyanti (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2023)
ABSTRACT        This study, to measure the factors that influence turnover intention are job satisfaction and work stress at PT. Hasnur Riung Sinergi, Tapin Regency, shows that the employee turnover rate tends to be high due to the high workload.The research objective is to find out and analyze the effect of job satisfaction and work stress on turnover intention at PT. Hasnur Riung Synergy of Tapin Regency.This research is a quantitative research with a correlational exploration method between the independent variables and the dependent variable. Research data was collected by questionnaire from 81 respondents. Then tested with the SPSS version 25 program.       The results of the study show that there is a partial and simultaneous effect of job satisfaction and work stress on turnover intention. The dominant variable in this study is job satisfaction.